Do entrepreneurial orientation influences business performance? case on youth entrepreneurs in Malaysia / Azlin Shafinaz Arshad and Zanariah Zainal Abidin - Arshad, Azlin Shafinaz; Abidin, Zanariah Zainal (2018)
Entrepreneurial orientation studies have received substantial attention from scholars and researchers all over the world. Many of these studies agree entrepreneurial orientation comprises of three constructs; innovativeness, proactiveness and risk-taking. Majority of these studies focused on Small and Medium Enterprises (SMEs) and examined the relationship between entrepreneurial orientation and business performance. This study attempts to investigate the relationship between entrepreneurial orientation and business performance from the perspectives of youth entrepreneurship in Malaysia. A quantitative approach using questionnaire is employed from youth entrepreneurs. Data were gathered from 477 youth entrepreneurs throughout Malaysia. The data was analysed using descriptive analysis and inferential analysis. The correlation analysis discovered the relationship between entrepreneurial orientation and its dimensions with business performance are positive and significant but with weak relationship. The results of multiple regression on the other hand described none of the entrepreneurial orientation dimensions are significant towards business performance. However, when measuring entrepreneurial orientation as a whole, the study found significant results with business performance. This study put forth suggestions for future researchers.